Pengaruh Kinerja Lingkungan, Pengungkapan Lingkungan, dan Biaya Lingkungan Terhadap Nilai Perusahaan - Silvia Aji Saputri; Betari Maharani; Wahyu Anggit Prasetya (Juara: Jurnal Riset Akuntansi, 2023)
The aims of this study are to investigate the effect of environment performance, environmental disclosure, and environment cost to firm value. Tobinâ€™s Q is used to measure firm value. This study is quantitative.Â  The data of this study had collected form financial statement in 2017-2021 period. The data population is manufactured company which registered in Bursa Efek Indonesia. This study used purposive sampling method to collect the data and we obtained 45 data sample. Regression analysis utilized to analysis the hypotheses. The result showed that environment performance has positive and significant effect to the firm value. Meanwhile, environment cost and environment disclosure had no effect on firm value.